LEGAL REPERCUSSIONS OF ILLEGAL LOGGING ON KERINCI SEBLAT NATIONAL PARK'S FOREST BIODIVERSITY (TNKS) - Shochifudin, Muhamad (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2025)
Illegal logging is like cancer eating away at the lungs of the earth; it seriously damages the sustainability of forests and the natural balance of the ecosystem. This illegal activity is a double-edged blade that harms the natural habitat of plants and animals while also violating the right to life of indigenous peoples. Illegal logging not only destroys biodiversity but also increases greenhouse gas emissions, causes erosion, and increases the likelihood of natural disasters. Because the social repercussions weaken indigenous peoples' rights and cause horizontal conflicts, they are particularly concerning. Fighting illicit logging requires the cooperation of the government, law enforcement, civil society organizations, and the general public. It is crucial to uphold stringent rules, encourage lifelong learning, and support the local economy of regions bordering forests.